Superovulation and embryo recovery in crossbred cows treated with single dose of FSH dissolved in polyvinyl pyrrolidone - SUBRAMANIAN, A; KRISHNAMOORTHY, P; MOHAN, P; BALASUBRAMANIAN, S (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to determine the superovulatory response and embryo recovery in crossbred cows treated with single dose of FSH dissolved in poly vinyl pyrrolidone (PVP). Nine crossbred cows were superovulated using single dose of FSH dissolved in 30% PVP and fourteen crossbred cows were superovulated using FSH multidose dissolved in saline. Donor cows were flushed non-surgically on day 7 after fixed time insemination with good quality semen, embryos recovered, examined, graded and cryopreserved until transfer. There was no significant difference between the two treatments of FSH in crossbred cows for number of corpus luteum, unovulated follicles, embryos recovered and transferable embryos. The rate of transferable embryos obtained were 85.0% and 86.9% in crossbred cows treated with single dose of FSH dissolved in PVP and multiple dose of FSH dissolved in saline respectively.